Methodological bases for designing electronic educational resources being the content of information educational environment - Smirnova, Iryna (Professional Pedagogics, 2015)
The article describes in detail aspects of methodological bases of development of electronic educational resources being the content of information and educational environment, which are necessary for a successful educational process at higher educational institutions of Ukraine. The author reveals the current information content and the overall capacity of network services that determine the required quality of the virtual environment of an educational institution. Objectives of implementing a modern virtual environment are clearly defined. A certain subsystem is singled out: a system of development and use of electronic educational resources at higher educational institutions. It is experimentally proved that integrally all functional systems are combined into a single information-educational environment of a higher educational institution. It is also proved that ITS provides an individual approach according to which a teacher of an education institution can developed for each student selected individual tasks (INDZ) on preparation for the work with the ESM, which provide pedagogical control and measurement. The study has reveald that the most important structural component and methodological basis for the development of information-educational environment of a higher educational institution is a set of electronic training and methodological support for educational discipline.
Keywords: electronic educational resources; IT - information technology; network services; electronic systems; information-educational environment